Eficácia e segurança dos antiangiogênicos no tratamento da retinopatia da prematuridade : revisão sistemática e metanálise - Ogata, Matheus Senna Pereira (2018)
Background: The standard treatment of retinopathy of prematurity (ROP) is the ablation of the avascular retina with laser or cryotherapy. However, this therapy may leave permanent structural and visual sequelae and may not be effective in cases of posterior and aggressive ROP. Vascular endothelial growth factor (VEGF) is involved in the pathogenesis of ROP, and antiangiogenic therapy is an option in cases of failure of standard treatment. The potential adverse effects of the use of antiangiogenic drugs in preterm neonates and the lack of concrete evidence on the efficacy of these drugs justify a systematic review of the literature. Objective: To evaluate the efficacy and safety of antiangiogenic therapy, when compared with laser photocoagulation, cryotherapy or combination therapy, in the treatment of ROP. Method: A systematic review of the literature was conducted using the Cochrane collaboration methodology and electronic search platforms to identify studies using antiangiogenic drugs in the treatment of ROP. The quality of the evidence was evaluated by the GRADE system (Grading of Recommendations Assessment, Development, and Evaluation). Results: Twelve studies were included in this review (six randomized controlled trials - RCTs and six non-randomized observational studies), including 677 preterm infants. Through the meta-analyzes, there was a statistical difference benefiting anti-VEGF therapy in the occurrence of progression to retinal detachment (RR 0.14 [95% CI 0.05, 0.38] p = 0.0001, I2 = 0%) and myopia occurrence (Weighted mean difference 0.25 [95% CI 0.14, 0.37] p <0.0001, I2 = 76%). At the end of ROP recurrence, there was a statistical difference benefiting the laser (RR 1.88 [95% CI 1.34, 2.63], p = 0.0003, I2 = 82%). There was, however, no difference between the anti-VEGF therapy and the laser in the occurrence of ocular complications (RR 0.84 [95% CI 0.34, 2.08] p = 0.71, I2 = 0%). In the subgroup analysis, in the comparison between the ROP involvement zones, the anti-VEGF presented a lower risk of recurrence requiring retreatment than the laser in premature infants with zone I ROP (RR 0.23 [95% CI 0.11, 0.49] p = 0.0001, I2 = 61%).The quality of the GRADE evidence varied from very low to low. Conclusions: There is evidence that anti-VEGF therapy, used as monotherapy, when compared to laser, reduces the risk of progression to retinal detachment, the occurrence of myopia, and the risk of recurrence of ROP in preterm infants with the disease in zone I.However, there is still a lack of quality evidence to attest to the safety of therapy, especially regarding potential systemic effects in preterm infants.